Analysis of Nutritional Program Implementation in Pregnant Women with Chronic Energy Deficiency with Increased Weight - Murti, Ida Ari; Idealistiana, Lia (GLOBAL HEALTH SCIENCE GROUP, 2024)
Chronic Energy Deficiency (CED/ KEK) is a nutritional problem in pregnant women that cannot be handled properly. So public health policies are needed that guarantee the availability of nutritious food for pregnant women, such as providing nutritious food for pregnant women, increasing the knowledge of pregnant women so they can provide food for their nutritional needs. The aim of this research is to analyze the implementation of nutritional programs in pregnant women with CED (chronic energy deficiency) with increased body weight. This research is a type of quasi-experimental research. The location used for this research was the Pabuaran Community Health Center, Serang Regency, Banten Province in December 2023. In this study, the population used was a limited population, namely all pregnant women registered in the